Risk factors for idiopathic sudden sensorineural hearing loss and their association with clinical outcome. Issue 3 (March 2015) - Passamonti, Serena M.; Di Berardino, Federica; Bucciarelli, Paolo; Berto, Valentina; Artoni, Andrea; Gianniello, Francesca; Ambrosetti, Umberto; Cesarani, Antonio; Pappalardo, Emanuela; Martinelli, Ida
Abstract Background Sudden sensorineural hearing loss (ISSHL) is idiopathic in 85% of cases and cochlear micro-thrombosis has been hypothesized as pathogenic mechanism. The role of thrombophilia and cardiovascular risk factors in ISSHL is controversial and whether these risk factors influence the clinical outcome of ISSHL is unknown. Methods and patients To investigate the role of thrombophilia and cardiovascular risk factors in ISSHL and to evaluate their influence on clinical outcome of the disease, 118 patients with a first episode of ISSHL and 415 healthy controls were investigated. Thrombophilia screening included measurements of antithrombin, protein C, protein S, factor V Leiden, prothrombin G20210A, antiphospholipid antibodies, fibrinogen, factor VIII and homocysteine. Results Deficiencies of antithrombin, protein C or S taken together, high factor VIII and hyperhomocysteinemia were significantly associated with ISSHL (OR [95%CI]: 7.55 [1.05-54.47], 2.91 [1.31-6.44] and 2.69 [1.09-6.62], respectively), whereas no association was found with the remaining thrombophilia markers. A 2-fold increased risk of poor clinical outcome was observed for every 5 μmol/L increase of fasting homocysteine levels (adjusted OR [95%CI]) 2.13 [1.02-4.44]) until levels of approximately 15 μmol/L, then the risk increased slowly. Cardiovascular risk factors (arterial hypertension, hyperlipidemia, diabetes and smoking) were associated with an increased risk of ISSHL (OR [95%CI] 1.88 [1.17-3.03]) and with a poor clinical outcome (OR [95%CI] 2.22 [0.93-5.26]). Conclusions Hyperhomocysteinemia, high factor VIII and, with more uncertainty, deficiencies of antithrombin, protein C or S and cardiovascular risk factors increase the risk of ISSHL. Hyperhomocysteinemia and cardiovascular risk factors are associated with a poor clinical outcome of ISSHL.